Microstructure evolution，thermal cycling lifetime， and failure behavior analysis of YSZ thermal barrier coatings prepared by EB-PVD with different electron beam currents - MU Rende; DING Ning; LIU Guanxi; LUO Yuqing; DAI Jianwei (Cailiao gongcheng)
The electron beam-physical vapor deposition （EB-PVD） technology was employed to fabricate yttria-stabilized zirconia （YSZ） thermal barrier coatings at different electron beam currents （1.2，1.8，2.4 A）. The phase structure and microstructural morphology of YSZ coatings at different electron beam currents were analyzed and characterized. The thermal barrier coatings were also subjected to a 1150 ℃ thermal cycling life test. The failure behaviors of coatings were analyzed by the evolution of the microstructure. The results show that YSZ coatings at different electron beam currents all possess a non-equilibrium tetragonal phase structure. As the electron beam current increases， the columnar grain tip structure of the coating evolves from a triangular shape to a pyramidal shape and then to a ridge-like shape， with the column structure changing from a slender structure to a coarse structure， the dendrites decreasing， and the arrangement becoming more orderly. The thermal conductivity is lower slightly due to the appearance of ordered nanopores in the column of YSZ coatings. The YSZ coating prepared at 1.8 A demonstrates the most excellent thermal shock life of 895 cycles， approximately twice that of the YSZ coating prepared at 1.2 A and 1.3 times that of the YSZ coating prepared at 2.4 A. The slender columnar grain structure prepared at a low electron beam current is prone to sintering failure， while the coarse columnar grain structure prepared at a high electron beam current is prone to thermally grown oxide （TGO） layer stress accumulation failure. The columnar grain structure prepared at 1.8 A could balance the two types of failure behaviors， effectively extending the thermal cycling life of the YSZ thermal barrier coating.